2013
DOI: 10.1002/chem.201202821
|View full text |Cite
|
Sign up to set email alerts
|

The Aqueous Ca2+ System, in Comparison with Zn2+, Fe3 +, and Al3 +: An Ab Initio Molecular Dynamics Study

Abstract: Herein, we report on the structure and dynamics of the aqueous Ca(2+) system studied by using ab initio molecular dynamics (AIMD) simulations. Our detailed study revealed the formation of well-formed hydration shells with characteristics that were significantly different to those of bulk water. To facilitate a robust comparison with state-of-the-art X-ray absorption fine structure (XAFS) data, we employ a 1st principles MD-XAFS procedure and directly compare simulated and experimental XAFS spectra. A compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 89 publications
8
34
0
Order By: Relevance
“…The average values of the distributions are rather different, namely about 3.00 D from the Wannier scheme and 2.40 D from the Bader scheme. The published values for the average Wannier-type dipole moment in liquid water are generally reported to lie close to 3.0 D for various AIMD simulations using PBE or BLYP-based functionals in the literature (a selection of references is found in [61][62][63]). On average the water molecule is thus enhanced by a factor of more than 60% compared to the gas-phase value.…”
Section: Molecular Dipole Momentmentioning
confidence: 81%
“…The average values of the distributions are rather different, namely about 3.00 D from the Wannier scheme and 2.40 D from the Bader scheme. The published values for the average Wannier-type dipole moment in liquid water are generally reported to lie close to 3.0 D for various AIMD simulations using PBE or BLYP-based functionals in the literature (a selection of references is found in [61][62][63]). On average the water molecule is thus enhanced by a factor of more than 60% compared to the gas-phase value.…”
Section: Molecular Dipole Momentmentioning
confidence: 81%
“…In the cited papers, the dipole moment values were always obtained from a Wannier center analysis calculated from the electronic wavefunction for selected snapshots from CPMD simulations using the PBE or BLYP functionals. Thus, Bogatko et al 12 also found a value of 2.8 D for K + (aq). There exist some additional papers in the literature where dipole moments for first-shell water molecules around cations have been calculated, but they have not been included in our graph since the OÁ Á ÁO distances between the first and second hydration shells were not reported or they were not easily calculated (by us) from the published data.…”
Section: Dipole Momentsmentioning
confidence: 89%
“…61 The quantum chemical statistical mechanical (QMSTAT) study by Tofteberg et al 58 reported a CN of 6.9 with a Ca-O length of 2.5 Å. Various CPMD 41,42,62,63 studies of the hydration structure of Ca 2+ calculated CN in the range 5.9 41 to 7.2 62 and Ca-O distances of 2.36 41 to 2.45 Å. 63 A BOMD study by Mehandzhiyski et al 64 found a CN of 7 with a Ca-O distance of 2.45 Å, in agreement with earlier CPMD studies.…”
Section: +mentioning
confidence: 99%
“…Each calculated trajectory was 20 ps long and was comprised of 40 000 steps, each of length 0.5 fs. The first 5 ps of each trajectory was treated as an equilibration period, in keeping with previous studies, 41,63,100,101,[138][139][140] and was not considered in subsequent analysis. It is worth noting that an alternative approach of performing initial classical MD simulations in the NPT ensemble using classical MD may lead to better equilibration.…”
Section: Computational Detailsmentioning
confidence: 99%